INTERNATIONAL SYMPOSIUM: "EVOLUTION OF PERMIAN MARINE BIOTA," AND PROBLEMS CONCERNING PERMIAN SECTIONS IN THE TYPE REGION - Chuvashov B.I.; Bogoslovskaya M.F.; Grunt T.A.; Leonova T.B.; Esaulova N.K.; Kanev G.P.; Chermnykh V.A. (My University, 1997)
The main results of the International Symposium "Evolution of Permian Marine Biota," are presented. The Artinskian to Ufimian part of the section at the Kozhim River (Polar Urals) is briefly described including its paleontological characteristics. Potentials for further study of Permian deposits in the Urals and possibilities of using the Uralian stages as international standards are discussed.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская